A hierarchal model of coding knowledge towards facilitating knowledge transfer in organizations. Issue 2 (16th June 2021) - Valmohammadi, Changiz; Rahmani, Farzaneh
Abstract : Purpose: This paper aims to present a hierarchal and operational model of coding knowledge towards facilitating the transformation of knowledge in organizations. Design/methodology/approach: The methodology used, is based on collaborative participation in knowledge coding that is widely used in large settings such as Wikipedia. Findings: Knowledge coding means the transfer of knowledge into a model which can be stored and shared. According to this definition, Knowledge can be accepted as a set of facts and the relationships among them. Through the suggested hierarchical model, primarily facts and initial entities are determined and knowledge record begins with the start of recording routines. In general, each routine is made up of simpler routines and facts. Thus the final model, which is a set of compound and complicated routines, can encode different levels of knowledge with different complexities. The suggested model in the explained processes is a conceptual model and a descriptive model in explaining facts. Research limitations/implications: Due to high-level programming expertise, in this paper, only the method of implementation of the proposed operational model has been explained. The proposed method maintains various advantages such as applicability, comprehensibility by different people in an organization, the possibility of knowledge coding at different levels, supporting abstract concepts besides operational ones and finally the possibility of implementing it by existing tools. Practical implications: The suggested model can be used for a variety of needs. For instance, in this paper, the first modelling example referred to a software concept, while the other referred to the implementation of an organizational process. Due to a hierarchy in describing knowledge, the suggested model can be used by any user with any level of knowledge (either user or registrar). Social implications: This method can create a change in social media and make it possible for anyone in any society with any level of information to share their knowledge at their own level and use the knowledge of others at the same level. Originality/value: The strength of the proposed model stems from its hierarchical nature which is considered for knowledge coding at different levels and includes advantages such as comprehensibility for different people in an organization, the possibility of knowledge coding at different levels and supporting abstract concepts in addition to operational ones.